Access to diagnosis, treatment, and supportive services among pharmacotherapy-treated children/adolescents with ADHD in Europe: data from the Caregiver Perspective on Pediatric ADHD survey - Fridman, Moshe; Banaschewski, Tobias (Neuropsychiatric disease and treatment, 2017)
Access to diagnosis, treatment, and supportive services among pharmacotherapy-treated children/adolescents with ADHD in Europe: data from the Caregiver Perspective on Pediatric ADHD survey Moshe Fridman,1 Tobias Banaschewski,2 Vanja Sikirica,3 Javier Quintero,4 Kristina S Chen5 1AMF Consulting, Inc., Los Angeles, CA, USA; 2Department of Child and Adolescent Psychiatry and Psychotherapy, Central Institute of Mental Health, Medical Faculty Mannheim of the University of Heidelberg, Mannheim, Germany; 3Global Health Economics Outcomes Research and Epidemiology, Shire, Wayne, PA, USA; 4Psychiatry Department, Hospital Universitario Infanta Leonor, Complutense University, Madrid, Spain; 5Global Health Economics Outcomes Research and Epidemiology, Shire, Lexington, MA, USA Background: Attention-deficit/hyperactivity disorder (ADHD) is one of the most common childhood psychiatric disorders and negatively impacts caregiver´s lives. Factors including barriers to accessing care, dissatisfaction with support services, and lack of caregiver resources may contribute to this. Objectives: To report caregiver´s experiences of ADHD diagnosis, behavioral therapy (BT), and supportive care for children/adolescents with ADHD.Methods: The Caregiver Perspective on Pediatric ADHD (CAPPA) survey included caregivers of children/adolescents (6-17 years) from ten European countries who were currently receiving/had received ADHD pharmacotherapy in the previous 6 months. Caregivers reported experiences of obtaining an ADHD diagnosis, access to BT, availability of caregiver resources, and level of health care/school support. Pan-EU and country-specific descriptive statistics are reported; responses were compared across countries.Results: Of 3,616 caregivers, 66% were female. Mean age of children/adolescents was 11.5 years; 80% were male. Mean time from the first doctor visit to diagnosis was 10.8 (95% confidence interval 10.2, 11.3) months; 31% of caregivers reported the greatest degrees of difficulty in obtaining an ADHD diagnosis; 44% of children/adolescents did not receive BT. Forty-seven percent of caregivers reported that sufficient resources were available, 44% were "very satisfied"/"satisfied" with medical care, and 50% found health care providers "very supportive"/"somewhat supportive". Mainstream schools were attended by 82% of children/adolescents. Of those, 67% of caregivers thought schools could help more with the child/adolescent´s ADHD and 48% received extra help/special arrangement. Results varied significantly between countries (P